Life among the Yanomami : the story of change among the Xilixana on the Mucajai River in Brazil - Peters, John F. (John Fred), 1935- (Broadview Press, 1998)
Life Among the Yanomami builds on literature and the author's personal experience of the northern Brazil people, the Mucajai Yanomami, with whom he lived from 1958 to 1967 and whom he has since frequently visited. The result is a rich and well-rounded understanding of this famously isolated people. While considerable detail of traditional way of life is provided, particular attention is devoted to the realities of social change arising from initial exposure to missionaries (of whom the author was one) to the more recent pressures from mining and the intervention of government and Non-Governmental Organizations (NGOs). Family and village life, health and health care, demography, politicization (that includes Yanomami criticism of Western Society), and on cultural survival are among the key issues explored by Peters-compelling issues for indigenous peoples the world over.